A High-Performance (14)c Accelerator Mass Spectrometry System - Roberts, M. L.; Burton, J. R.; Elder, K. L.; Longworth, B. E.; McIntyre, C. P.; von Reden, K. F.; Han, B. X.; Rosenheim, B. E.; W. J. Jenkins; Galutschek, E.; McNichol, A. P. (Radiocarbon, 2010)
A new and unique radiocarbon accelerator mass spectrometry (AMS) facility has been constructed at the Woods Hole Oceanographic Institution. The defining characteristic of the new system is its large-gap optical elements that provide a larger-than-standard beam acceptance. Such a system is ideally suited for high-throughput, high-precision measurements of (14)C. Details and performance of the new system are presented.
id: 2095; PT: J; CT: 20th International Radiocarbon Conference; CY: MAY 31-JUN 05, 2009; CL: Big Isl, HI; SI: 1; UT: WOS:000285437800005